2010
DOI: 10.3109/07420528.2010.516048
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Nocturnal Nonvisual Responses to Monochromatic and Polychromatic Light With a Melanopsin Photosensitivity Function

Abstract: The short-wavelength (blue) light sensitivity of human non-visual responses is recognised as being melanopsin-based. However, whether melanopsin is the sole factor in determining the efficacy of a polychromatic light source in driving non-visual responses remains to be established. Monochromatic (λ max 437, 479 and 532 nm) and polychromatic (colour temperature: 4000 K and 17000 K) light stimuli were photon matched for their predicted ability to stimulate melanopsin, and their capacity to affect nocturnal melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…Suppression of melatonin by exposure to evening light may be an underlying mechanism by which light acutely increases alertness, as seen in the present study and in previous reports (14)(15)(16)(17)(18)(19). Other studies, however, have not found a relationship between alertness and melatonin levels during light exposure (20,21) or have shown changes in alertness induced by light exposure during the day, when melatonin levels are at low or undetectable levels (22)(23)(24).…”
Section: Discussionsupporting
confidence: 79%
“…Suppression of melatonin by exposure to evening light may be an underlying mechanism by which light acutely increases alertness, as seen in the present study and in previous reports (14)(15)(16)(17)(18)(19). Other studies, however, have not found a relationship between alertness and melatonin levels during light exposure (20,21) or have shown changes in alertness induced by light exposure during the day, when melatonin levels are at low or undetectable levels (22)(23)(24).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, a b/y pathway originates in the small bistratified RGCs and associated interneurons that combine excitation from S-cones and inhibition from (L + M)-cones [39]. Therefore, the responses of ipRGCs activated by S-cones might be reduced by inhibition from (L + M)-cones on simultaneous exposure to blue and green light, and NIF functions might show subadditivity to some types of polychromatic light [3234] and two simultaneous exposures to monochromatic light [29], as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is called the subadditive response to light [29]. Figueiro et al [32, 33] and Revell et al [34] also identified the subadditive effects of monochromatic and polychromatic light on melatonin suppression, suggesting that cones affected the ipRGC response. However, it remains unclear whether the subadditive response affects pupillary constriction.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that a more recent study of melatonin suppression using monochromatic lights with matched photon density found a peak at 480 nm (Najjar et al, 2014), suggesting that melanopsin makes the dominant contribution. Nonetheless, two studies investigating melatonin suppression by exposure to different polychromatic light sources have provided evidence for sub-additive responses that could be indicative of cone-opponent inputs (Figueiro et al, 2004; Revell et al, 2010), although a follow up study by the authors of one of those papers failed to find an opponent effect of combining short and long wavelength monochromatic stimuli (Papamichael et al, 2012). One model of the human circadian system explicitly includes an S-opponent input (Rea et al, 2010) but the evidence supporting such a role is far from conclusive.…”
Section: Chromatic Circadian Photosensitivity In Mammalsmentioning
confidence: 99%